Interaction Dynamics of Caffeine in the Human Acetylcholinesterase Binding Pocket - Wiranata, Bonifacius Ivan; Istyastono, Enade Perdana (Journal of Food and Pharmaceutical Sciences, 2025)
Alzheimer’s disease (AD) cases are increasing in Indonesia, with no effective therapy due to multiple hypotheses about its causes. The cholinergic hypothesis, focusing on acetylcholinesterase (ACHE) inhibition, is a key therapeutic approach. Caffeine, a natural compound, shows a potent activity as an AChE inhibitor. This study used computational methods to investigate the interaction dynamics of caffeine with the AChE’s active site. This study performed 100 redocking simulations of donepezil to validate the docking protocol followed by 100 molecular docking simulations of caffeine. The 50-ns molecular dynamics (MD) production phase simulations of donepezil and caffeine were performed to study the interaction dynamics, such as conformational stability and binding free energies. The interaction hotspots during the simulations were identified using PyPLIF HIPPOS. Our findings reveal that caffeine interacted in the active site during the simulations and the importance of Glu202 and Phe338 in helping caffeine reside within the esteratic site of AChE.